2022
DOI: 10.3390/vaccines10101727
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Nanotechnology for Cancer Immunoprevention and Immunotherapy: A Review

Abstract: One of the most effective cancer therapies, cancer immunotherapy has produced outstanding outcomes in the field of cancer treatment. However, the cost is excessive, which limits its applicability. A smart way to address this issue would be to apply the knowledge gained through immunotherapy to develop strategies for the immunoprevention of cancer. The use of cancer vaccines is one of the most popular methods of immunoprevention. This paper reviews the technologies and processes that support the advantages of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 223 publications
0
4
0
Order By: Relevance
“…In the world of medicine, complex and incurable diseases such as cancer are always given a special focus to find treatment and early diagnosis options for these modalities [ 113 ]. Nanotechnology is providing a good opportunity for researchers to develop such nano-agents, fluorescent materials, molecular diagnostics kits, and specific targeted drugs that may help to diagnose and cure disease in a better way in the future [ 114 ].…”
Section: Results and Discussion—applications Of Nanotechnology In The...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the world of medicine, complex and incurable diseases such as cancer are always given a special focus to find treatment and early diagnosis options for these modalities [ 113 ]. Nanotechnology is providing a good opportunity for researchers to develop such nano-agents, fluorescent materials, molecular diagnostics kits, and specific targeted drugs that may help to diagnose and cure disease in a better way in the future [ 114 ].…”
Section: Results and Discussion—applications Of Nanotechnology In The...mentioning
confidence: 99%
“…Nanotechnology is providing a good opportunity for researchers to develop such nano-agents, fluorescent materials, molecular diagnostics kits, and specific targeted drugs that may help to diagnose and cure disease in a better way in the future [ 114 ]. Scientists are trying various protocols to conjugate already available drugs with nanoparticles to enhance drug specificity and targeting in organs [ 113 , 114 , 115 ].…”
Section: Results and Discussion—applications Of Nanotechnology In The...mentioning
confidence: 99%
“…The chimeric antigen receptor T cell (CAR-T cell) is one of the prominent applications of immunotherapeutic plasmids [ 59 ]. Cells are treated with plasmid DNA to elicit immune responses against the encoded antigen [ 60 ]. Early research using mice showed that plasmid DNA may trigger immune responses against cancer, influenza, and HIV-1 transgenic products, establishing DNA as a viable vaccination platform [ 61 ].…”
Section: Nucleic Acid Types and Structurementioning
confidence: 99%
“…In recent years, nanoparticle drug delivery systems have displayed tremendous potential in cancer immunotherapy. Especially, with a deeper understanding of the biological process in vivo of drug delivery system and mechanism of tumor immune escape, cell-derived biomimetic nanodelivery systems (BNDS) have been designed to improve the therapeutic potential and decrease adverse reaction . Interestingly, BNDS can ideally overcome the diversiform obstacles due to their biological characteristics.…”
Section: Introductionmentioning
confidence: 99%